2021
DOI: 10.3390/ani11020476
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Selected Prebiotics or Synbiotics Administered in ovo on Lymphocyte Subsets in Bursa of the Fabricius, Thymus, and Spleen in Non-Immunized and Immunized Chicken Broilers

Abstract: The effects of in ovo-delivered prebiotics and synbiotics on the lymphocyte subsets of the lymphoid organs in non-immunized 7-day-old broiler chickens and in non-immunized, sheep red blood cells (SRBC)-immunized, and dextran (DEX)-immunized 21- and 35-day-old birds were studied. The substances were injected on the 12th day of egg incubation: Prebiotic1 group (Pre1) with a solution of inulin, Prebiotic2 group (Pre2) with a solution of Bi2tos (non-digestive transgalacto-oligosaccharides), Synbiotic1 group (Syn1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…A healthy gut has been associated with low pathogen loads primarily of commercial concern, such as Eimeria, Coccidiosis, and Clostridium ( Luo et al, 2013 ), and consequently low flock disease burden. Other than vaccinations, immunity indices can be modulated through feeding bioactives such as yeast and yeast derivatives ( Szczypka et al, 2021 ; Vailati-Riboni et al, 2021 ). We observed that feeding yeast to YBC increased jejunal and plasma IgA, an immune protein associated with health resilience, especially concerning the humoral immune system of the intestinal environment.…”
Section: Discussionmentioning
confidence: 99%
“…A healthy gut has been associated with low pathogen loads primarily of commercial concern, such as Eimeria, Coccidiosis, and Clostridium ( Luo et al, 2013 ), and consequently low flock disease burden. Other than vaccinations, immunity indices can be modulated through feeding bioactives such as yeast and yeast derivatives ( Szczypka et al, 2021 ; Vailati-Riboni et al, 2021 ). We observed that feeding yeast to YBC increased jejunal and plasma IgA, an immune protein associated with health resilience, especially concerning the humoral immune system of the intestinal environment.…”
Section: Discussionmentioning
confidence: 99%
“…lactis was the most effective stimulator to the immune system [111] Prebiotics Galactooligosaccharides (3.5 mg/egg) Air cell on day 12 of incubation Galactooligosaccharides administered in ovo down-regulated the expression of immune-related genes that were activated by heat stress.…”
Section: Air Cell On Day 12 Of Incubationmentioning
confidence: 99%
“…While most of the immune system development in broilers happens early in life, it is essential to have access to the bioactive compounds that can enhance the development and maturation of the immune system. Probiotics and prebiotics have the ability to stimulate the proper development of the immune system [ 18 , 111 , 112 ]. Moreover, early stimulation of the gut microbiota via supplementation with probiotics, prebiotics, or their combination can enhance the productivity and health of newly hatched chicks [ 14 , 113 , 114 ].…”
Section: In Ovo Technique As a Novel Tool For Early-life Programmingmentioning
confidence: 99%
See 2 more Smart Citations